The death of the shtetl - Bauʾer, Yehudah 1926- (Yale Univ. Press, 2009)
Background -- The thirties -- The Soviet occupation -- The Holocaust in the kresy -- The shtetl community and its leadership, 1941-1943 -- The neighbors -- Rebels and partisans -- The death of the shtetl